The Influence of Service Innovation, University Reputation on Student Satisfaction: Academic Culture as a Mediator at Universitas Khairun - Ida Hidayanti; Johan Fahri; Fadhliah M. Alhadar (Journal of International Conference Proceedings (JICP), 2022)
Education is one of the driving forces for progress in the global community, one of which is through the emergence of innovations. With innovations in various fields of science and knowledge, changes have emerged that can positively impact people's lives. Higher Education, as one of the places of development of science, is a very appropriate place to develop innovations, both in the technological and social fields. On the other hand, changes in people's mindsets and behaviors demand changes in higher education institutions. The rapid development of science, supported by technological advances, demands changes in education and teaching patterns, including in higher education. With information disclosure and existing social and technological changes, science can develop further and more rapidly if the education system can adjust to the changes.This study used a survey method with the distribution of questionnaires. The population of the study was students of Khairun University. Sample takers with non-probability sampling method, by convenience sampling. The analysis method used in this study used Smart PLSVersion 3.0The results showed that out of 10 hypotheses, five hypotheses were accepted, and five hypotheses were rejected.Keywords: Service Innovation, University Reputation, Academic Culture, University Student Satisfaction